Privatization process and talent management in Angola - Lopes da Costa, R.; Sampaio. M.; Miguel, I. (Journal of Reviews on Global Economics, 2019)
The problem of the privatization process began in the 1940s, even though it only really began to gain a prominent place in the entrepreneurial path, about 50 years later. The processes of privatization of the world economies, which led to the triggering of a set of cooperative strategies based on the State-owned enterprises privatization, and, of course, all these events, had repercussions also in Angola. Based on an investigation of a pragmatic or inductive nature, based on a non-probabilistic sample, due to the lack of studies and information about the phenomenon of Angola’s privatization during the period from colonial independence to the present. This article aims to develop this subject by presenting, on the one hand, a set of causes that were the basis of the failure in the privatization processes taken place in Angola between 1989 and 2005 and which degenerated into the collapse of its corporate network. And, on the other hand, it presents an idea of the possible impact that these privatization processes failures had, and still have, on Talent Management by Angolan organizations. It also presents a set of suggestions which could be considered in future privatization processes that may occur by building a more consistent business structure in economic and business terms.